Tratamento de efluentes da carcinicultura por flotação em coluna e flotação. - Melo, José Francisco de Araújo (2010)
The high productivity in the breeding of shrimp makes it necessary to approach some aspects to their sustainability, particularly the aquatic environment of the nursery. Thus, the treatment of effluents originating from the shrimp becomes of fundamental importance, considering the need to minimize the environmental impacts generated by this productive activity. This study investigates the uses of flotation types of column and dissolved air to the treatment of shrimp effluent. The effluent used was from the farm Tabatinga, located on the north coast of Pernambuco State. Was performed physical-chemical and microbiological characterization of effluent being obtained parameters consistent with those found in the literature. A column flotation bench was used in experimental trials, being employed an experimental design with two variables (pH and air flow) to evaluate the removal of turbidity of the effluent. The effect of adding a flocculant was also investigated. The FAD cell experiments were performed with pressure values of 3 and 6 bar, and a pH of 5.8 and 9.8, and additional experiments were performed using an anionic collector. The results of column flotation for the effluent from the beginning of culture showed that the turbidity decreases with increasing air flow and the decrease in pH after 40 minutes of the proceedings, was obtained as best fit a linear model with interaction. The presence of flocculant concentration of 0.1% (p / v) at pH 7.8 showed a removal of turbidity of only 25% for the condition of lower air flow. For the treatment of effluent from the end of cultivation, the turbidity removal also increased with increasing air flow and with decreasing pH, reaching a maximum removal of about 40% after 35 minutes of the proceedings, with an adjustment quadratic model. In dissolved air flotation effluent end of the cultivation, the highest percentage of turbidity removal were obtained at pH 5.8, reaching values of 52 and 47% for operating pressures of 3 and 6 bar, respectively. In the presence of an anionic collector, there was an increase in the removal of turbidity values between 56 and 65%.